Reliability of 3D upper limb motion analysis in children with obstetric brachial plexus palsy. (13th February 2017) - Mahon, Judy; Malone, Ailish; Kiernan, Damien; Meldrum, Dara
Abstract: Kinematics, measured by 3D upper limb motion analysis (3D-ULMA), can potentially increase understanding of movement patterns by quantifying individual joint contributions. Reliability in children with obstetric brachial plexus palsy (OBPP) has not been established. Objective: This study aimed to determine between session reliability and measurement errors of 3D-ULMA using the acromion method (AM) in children with OBPP. Approach: Ten participants (mean 10 years, range 7–15 years, Narakas classification I–III) completed 3D-ULMA on two occasions, mean interval of 8.6 d (±2.8 d). Kinematic data were captured by a 4-CODA cx1 optoelectronic tracking system. Participants performed three trials of the modified Mallet scale tasks. Local coordinate systems, segment and joint rotations were defined as recommended by the International Society of Biomechanics. The intraclass correlation coefficient (ICC 2, K) and standard error of measurement (SEM) were calculated for task duration, range and joint angle at point of task achievement (PTA). Main Results: Results indicated poor reliability for spatiotemporal parameters and range. Moderate to excellent reliability at PTA was observed in 19/60 variables (ICC: 0.77–0.98; SEM: 3.5°–10.4°). The Abduction Task had the highest (ICC: 0.79–0.98; SEM: 3.5°–10.3°) with External Rotation the lowest reliability. Glenohumeral and thoracohumeral elevation had the most consistent reliability. Scapular protraction/retraction had consistently poor reliability (ICC: 0–0.72; SEM: 3.5°–10.2°) with axial rotation also poor (ICC: 0.00–0.91; SEM: 6.3°–32.8°). This study determined inconsistent test–retest reliability of 3D-ULMA, using AM, to track dynamic performance of functional tasks in children with OBPP. It is the first study to outline measurement error in this population. This information permits more reliable interpretation of future studies of kinematic patterns in children with OBPP.